LAMA GANG BENGKOK MOSQUE AS A MULTIETHNIC SYMBOL IN THE CITY OF MEDAN. - Raini Tanjung; Rudiansyah Rudiansyah; Jessy Chen (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2019)
LAMA GANG BENGKOK MOSQUE AS A MULTIETHNIC SYMBOL IN THE CITY OF MEDAN.Raini Tanjung; Rudiansyah; JessyProgram Studi Sastra Cina Fakultas Ilmu BudayaUniversitas Sumatera Utara ABSTRACTThe title of this research is ‘Lama Gang Bengkok Mosque As A Multiethnic Symbol In The City Of Medan’. The purpose of this study was to analyze the ornamental and symbolic forms of the Lama Gang Bengkok Mosque building, and explain the history of the Lama Gang Bengkok  Mosque which was used as a multiethnic symbol in Medan City. The method used is a qualitative research method and described descriptively. The theory used in this study is the semiotic theory of Charles Sanders Peirce. Data was obtained through observation and interview techniques with several informants and people around. The results showed that this building became one of the multiethnic symbols of harmony between religious and cultured people from ancient times to the present, and can be seen from the form and symbolism of the Lama Gang Bengkok Mosque building, such as the forms and symbols of Malay, Chinese and Persian culture.Keywords: Lama Gang Bengkok mosque; Ornaments; symbolis; Multi-Language; Medan City.